2014
DOI: 10.1111/head.12344
|View full text |Cite
|
Sign up to set email alerts
|

Bullying Victimization at School and Headache: A Meta‐Analysis of Observational Studies

Abstract: Background and objectives.-Being bullied at school is a risk factor for a variety of negative consequences, including somatic problems. The purpose of this meta-analysis is to determine the association between peer victimization and headache in the school-age population.Methods.-A systematic literature search was conducted in September 2013 to identify observational studies that examined the association between being bullied and headache in children and adolescents. Odds ratios (OR) were pooled by using a rand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
62
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(71 citation statements)
references
References 57 publications
5
62
1
2
Order By: Relevance
“…Recently, exposure to interpersonal violence has been posed as potential triggers of headache in adults [3, 103] and adolescents [31, 33, 97] although documentation is scarce [65, 75]. …”
Section: Possible Pathways In Development and Maintenance Of Psychopamentioning
confidence: 99%
“…Recently, exposure to interpersonal violence has been posed as potential triggers of headache in adults [3, 103] and adolescents [31, 33, 97] although documentation is scarce [65, 75]. …”
Section: Possible Pathways In Development and Maintenance Of Psychopamentioning
confidence: 99%
“…Evidence is mounting to suggest that victims of peer abuse not only experience serious mental health problems but also suffer from physical health consequences. Studies have already found that victimized children are more likely to report headaches, abdominal pain, sore throats, colds, and mouth sores than their non-victimized peers, even after controlling for initial health differences (Fekkes, Pijpers, & Verloove-Vanhorick, 2006;Gini, Pozzoli, Lenzi, & Vieno, 2014;Nixon, Linkie, Coleman, & Fitch, 2011;Rigby, 1998;Wolke, Woods, Stanford, & Schulz, 2001). In addition, victimized children are more likely to take pain medication (Due, Hansen, Merlo, Andersen, & Holstein, 2007) and visit the school nurse due to illness, as compared to non-victimized children (Vernberg, Nelson, Fonagy, & Twemlow, 2011).…”
Section: Physical Health Problemsmentioning
confidence: 99%
“…Kiusaamisessa osallisena olevilla lapsilla on todettu enemmän psykosomaattisia oireita (13,14,15,(37)(38)(39)(40)(41) sekä psyykkisiä ja sosiaalisia ongelmia (12,39,41,42) verrattuna ei kiusattuihin ikätovereihin. Kiusatuilla lapsilla on havaittu monenlaisia oireita: päänsärkyä (38), vatsakipua (13,37,43,44), yö-kastelua (13,43), alakuloisuutta, univaikeuksia (13,15,43), jännittyneisyyttä, huimausta, väsy-mystä (15) sekä huonoa ruokahalua (13,45). Kiusatut ovat raportoineet myös masennusoireista (13,47), heikosta itsetunnosta (46), ahdistuksesta (13,37) sekä yksinäisyydestä (47).…”
Section: Koulukiusaamisen Yhteys Oireiluununclassified